The Effectiveness of Fiat Fractional Reserve system and the role of Centralised Cryptocurrency on Economic Stability in Nigeria’s Digital Economic System - Saidu Alhaji , Sani; Bakari Mauda, Ahmed; Umar Jarengol, Isa; Bubba, Mohammed Bawuro (Summa : Journal of Accounting and Tax, 2024)
The study is aimed at assessing the effectiveness of fiat fractional reserve system and the role of centralised cryptocurrency on economic stability in Nigeria’s digital economic system The study adopted a qualitative means of data collection. The study uses Nigeria as the study area which was selected using purposive sampling technique. The qualitative information was collected using a semi-structured interview questions from the sampled participants. The collected information from qualitative source was analysed using thematic analyses with the aid of AtlasTi. The study found that the major challenges of the current fiat and fractional reserve system are rising cost of living, private money creation and overwhelming increase in public debt caused by interest rate manipulation. It was also found that the adoption of an alternate transactional system is timing considering the advancement in technology as the block-chain aided technology system will be a better option considering its security, transparency, controllability and traceability of all transactions operated on it. The study recommends that government especially policy makers should think on improving or modifying the current system so as to have a better system that will address the private money creation, unregulated transaction, interest rate manipulation. On the same vein the study recommends that centralized cryptocurrency transactional system should be adopted as a central transactional system which could be capable of minimizing oversupply of money through eradicating private money creation and interest rate manipulation.